The effect of prosocial behaviours on Chinese undergraduate nursing students' subjective well‐being: The mediating role of psychological resilience and coping styles. (27th October 2022) - Wan, Xiao; Huang, Haitao; Zhang, Yiming; Peng, Qianwen; Guo, Xiajun; Wu, Sijia; Li, Yuanyuan; Ding, Yueming; Chen, Chaoran
Abstract: This study aimed to explore the effect of prosocial behaviours on Chinese undergraduate nursing students' subjective well‐being (SWB) and examine the roles of psychological resilience and coping styles. The sample for this study included 683 nursing students from two undergraduate universities in Henan Province, China. SWB, prosocial behaviours, psychological resilience, and coping styles were assessed by the Index of Well‐Being, the Prosocial Behavioural Tendency Scale, the Connor‐Davidson Resilience Scale, and the Simplified Coping Style Questionnaire, respectively. We adopted Pearson's correlation analysis and the PROCESS Macro Model 81 in regression analysis to explore the relationships among prosocial behaviours, psychological resilience, coping styles, and SWB. Prosocial behaviours of undergraduate nursing students had a positive predictive effect on SWB; psychological resilience and coping styles both were the mediating variable between prosocial behaviours and undergraduate nursing students' SWB; psychological resilience and coping styles played a chain mediating role between the prosocial behaviours and SWB of undergraduate nursing students. The results indicated that prosocial behaviours not only directly affected the SWB of undergraduate nursing students but also affected the SWB of undergraduate nursing students via psychological resilience and coping styles. These results offer certain theoretical support and guidance for the research and improvement of undergraduate nursing students' SWB and emphasize the importance of interventions to increase prosocial behaviours, improve psychological resilience, promote positive coping styles, and address negative coping styles.